Seba Baduy: Komunikasi Antarbudaya dan Eksistensi Masyarakat Adat Kanekes - Pitriyani; Wilodati (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2024)
The importance of government recognition of customary law as part of Indonesia's cultural diversity. Communication and relations between the Kanekes community and the government are a fixed price that must be carried out through the Seba ceremony in order to maintain peace and harmony for all parties. The aim of this article is to find out the meaning of the Seba ceremony as intercultural communication and the existence of the Kanekes traditional community amidst the diversity of Indonesian society. This article uses a literature review research method. The results of the study show that the Seba tradition contains the meaning of gratitude and respect for the government as their leader. The Seba tradition has the following functions: (1) religious/ritual function, (2) traditional function and local wisdom of Pikukuh Karuhun, (3) social function, (4) political function and (4) cultural existence function.